Microtubule plus-end tracking Adenopolyposis Coli negatively regulates proplatelet formation. Issue 1 (December 2018) - Strassel, C.; Moog, S.; Mallo, L.; Eckly, A.; Freund, M.; Gachet, C.; Lanza, F.
Abstract Platelets are produced upon profound reorganization of mature megakaryocytes (MK) leading to proplatelet elongation and release into the blood stream, a process termed thrombopoiesis. This highly dynamic process requires microtubules (MT) reorganization by mechanisms that are still incompletely understood. Adenomatous polyposis coli (APC) is a microtubule plus-end tracking protein involved in the regulation of MT in a number of cell systems and its inactivation has been reported to alter hematopoiesis. The aim of our study was to investigate the role of APC in megakaryopoiesis and the final steps of platelet formation. Down-regulation of APC in cultured human MK by RNA interference increased endomitosis and the proportion of cells able to extend proplatelets (68.8% (shAPC1) and 52.5% (shAPC2) vs 28.1% in the control). Similarly an increased ploidy and amplification of the proplatelet network were observed in MK differentiated from Lin- cells of mice with APC-deficiency in the MK lineage. In accordance, these mice exhibited increased platelet counts when compared to wild type mice (1, 323 ± 111 vs 919 ± 52 platelets/µL; n = 12 p 0.0033**). Their platelets had a normal size, ultrastructure and number of microtubules coils and their main functions were also preserved. Loss of APC resulted in lower levels of acetylated tubulin and decreased activation of the Wnt signaling pathway. Thus, APC appears as an important regulator of proplatelet formation and overall thrombopoiesis.